2008
DOI: 10.1088/0022-3727/41/15/155504
|View full text |Cite
|
Sign up to set email alerts
|

Selective source reduction to identify masked sources using time reversal acoustics

Abstract: The presence of strong sources of elastic waves often makes it impossible to localize weaker ones, which are sometimes the most meaningful, e.g. in the characterization of complexity of active Earth faults or of microdamage in a composite structural material. To address this problem, a selective source reduction method is proposed here which, applied in conjunction with time reversal acoustics (TRA), provides the means to selectively reduce the contribution of strong sources allowing full illumination of the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…This paper has provided important experimental verifications of the SSR method using TR, which was proposed by Scalerandi et al 9 It has been shown that a weaker secondary source, which is masked by a stronger dominant source, may be illuminated, by employing the SSR method, based on subtraction of the dominant source direct arrival and coda. SSR has application in the detection of complex microcrack distributions in mechanical parts ͑NDE of solid materials͒ and possibly in the spatial/temporal characterization of complex earthquake sources.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…This paper has provided important experimental verifications of the SSR method using TR, which was proposed by Scalerandi et al 9 It has been shown that a weaker secondary source, which is masked by a stronger dominant source, may be illuminated, by employing the SSR method, based on subtraction of the dominant source direct arrival and coda. SSR has application in the detection of complex microcrack distributions in mechanical parts ͑NDE of solid materials͒ and possibly in the spatial/temporal characterization of complex earthquake sources.…”
Section: Discussionmentioning
confidence: 87%
“…Note that this remnant of focusing at S 1 also occurs in modeling experiments ͓see Figs. 6͑a͒, 7͑a͒, 9͑a͒, and 10͑a͒ in the paper by Scalerandi et al 9 ͔. The fact that the remnant is also manifested in modeling results, where the transducers were not included in the model, suggests that an imperfect TR reconstruction can also result in the focusing remnant at S 1 .…”
Section: A Source Reconstruction Issuesmentioning
confidence: 93%
See 3 more Smart Citations